The effect of culture on home-ownership - Miriam Marcén; Marina Morales (Global Labor Organization (GLO), 2018)
In this paper, we analyze the role of culture in determining whether, or not, an individual is a homeowner. We use data on first-generation immigrants who arrived in the United States under 6 years old. Following the epidemiological approach, those early-arrival immigrants grew up under the same US laws, markets, and institutions, so any dissimilarity in the proportion of homeowners by country of origin may be interpreted as a consequence of cultural differences. Our estimates indicate that there is a positive and statistically significant relationship between the cultural proxy, that is, the proportion of individuals who are homeowners by country of origin, and the immigrants' choice of home-ownership. Results are maintained after controlling for home-country observable and unobservable characteristics, and are consistent in several subsamples. Neither the differences in the formation of couples (same or different origin) nor the existence (or not) of mortgage financing appear to be driving our findings. Additionally, we present evidence of different mechanisms of transmission of culture (horizontal transmission, respect for elders, and gender roles), which reinforces our results on the cultural effect.
Keywords: J15; R20; Z13; 330; Culture; Immigrants; Home-ownership